Trust-supply chain performance relationships: unraveling the mediating role of transaction cost attributes in agribusiness SMEs - Owot, Godfrey Moses; Okello, Daniel Micheal; Olido, Kenneth; Odongo, Walter (Frontiers in Sustainable Food Systems, 2023)
The mediation effect of transaction cost attributes on the trust-supply chain performance relationships has remained largely under explored. Particularly little is known about the mediating role of information sharing, uncertainty and transaction frequency on the trust-supply chain performance relationships in agri-food sector. Results show that while trust positively influences supply chain performance, information sharing is the only transaction cost attribute that mediate the relationship between trust and supply chain performance. Agribusiness managers therefore need to not only renew effort of sharing accurate and timely information regarding the market's demand for specific volumes and quality of agricultural products, market trends and storage facilities, but also utilize the information to become competitive and improve supply chain performance.